Transparency in Buyer-Determined Auctions: Should Quality be Private or Public? - Sebastian Stoll; Gregor Zöttl (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We study non-binding procurement auctions where both price and non-price characteristics of bidders matter for being awarded a contract. The outcome of such auctions critically depends on how information is distributed among bidders during the bidding process. As we show theoretically, whether it is in the buyer's interest to conceal or to disclose non-price information most importantly depends on how important the quality aspects of the good to be procured are to the buyer: The more important the quality aspects are to the buyer, the more interesting concealment becomes. We then empirically study the impact of a change in the information structure using data from a large European online procurement platform for different categories of goods. In a counterfactual analysis we analyze the reduction of non-price information available to the bidders. In the data we find that the choice of information structure indeed matters. Confirming the hypothesis obtained in our theoretical framework, we find that in auction categories where bidders' non-price characteristics are of little importance for the decisions of the buyers, concealment of non-price information decreases buyers' welfare by up to 6% due to reduced competitive pressure leading to higher bids. In contrast, for categories where bidders' non-price characteristics strongly influence buyers' decisions concealment of non-price information increases buyers' welfare by up to 15%.
urn:nbn:de:bvb:19-epub-20862-6
Keywords: 330; Procurement; Non-Binding Auctions; Supply Chain Management